Co-utilization of glucose and xylose for the production of poly-β-hydroxybutyrate (PHB) by Sphingomonas sanxanigenens NX02 - Yue Ming; Guoqiang Li; Zhuangzhuang Shi; Xin Zhao; Yufei Zhao; Ge Gao; Ting Ma; Mengmeng Wu (Microbial Cell Factories, 2023)
Abstract Background Poly-β-hydroxybutyrate (PHB), produced by a variety of microbial organisms, is a good substitute for petrochemically derived plastics due to its excellent properties such as biocompatibility and biodegradability. The high cost of PHB production is a huge barrier for application and popularization of such bioplastics. Thus, the reduction of the cost is of great interest. Using low-cost substrates for PHB production is an efficient and feasible means to reduce manufacturing costs, and the construction of microbial cell factories is also a potential way to reduce the cost. Results In this study, an engineered Sphingomonas sanxanigenens strain to produce PHB by blocking the biosynthetic pathway of exopolysaccharide was constructed, and the resulting strain was named NXdE. NXdE could produce 9.24 ± 0.11 g/L PHB with a content of 84.0% cell dry weight (CDW) using glucose as a sole carbon source, which was significantly increased by 76.3% compared with the original strain NX02. Subsequently, the PHB yield of NXdE under the co-substrate with different proportions of glucose and xylose was also investigated, and results showed that the addition of xylose would reduce the PHB production. Hence, the Dahms pathway, which directly converted D-xylose into pyruvate in four sequential enzymatic steps, was enhanced by overexpressing the genes xylB, xylC, and kdpgA encoding xylose dehydrogenase, gluconolactonase, and aldolase in different combinations. The final strain NX02 (ΔssB, pBTxylBxylCkdpgA) (named NXdE II) could successfully co-utilize glucose and xylose from corn straw total hydrolysate (CSTH) to produce 21.49 ± 0.67 g/L PHB with a content of 91.2% CDW, representing a 4.10-fold increase compared to the original strain NX02. Conclusion The engineered strain NXdE II could co-utilize glucose and xylose from corn straw hydrolysate, and had a significant increase not only in cell growth but also in PHB yield and content. This work provided a new host strain and strategy for utilization of lignocellulosic biomass such as corn straw to produce intracellular products like PHB.